2022
DOI: 10.3389/fneur.2022.996580
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular dysfunction in pediatric patients with cochlear implantation: A systematic review and meta-analysis

Abstract: ObjectiveVestibular dysfunction may delay the achievement of balance and perception milestones in pediatric patients after cochlear implantation (CIM).MethodsA strategic literature search was done following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. We searched the PubMed, Medline, Embase, Web of Science, and Cochrane Library databases from inception to July 2022. Studies were included on the otoliths, semicircular canals, and balance function changes in children af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 76 publications
0
0
0
Order By: Relevance
“…In addition to the data referring to children with SNHL, this study also analyzed five children using cochlear implants, and all of them presented dysfunctions in the vestibular system and postural instabilities in the stabilometric evaluation. These findings corroborate those of other studies, which found vestibular dysfunctions [ 105 , 106 , 107 , 108 , 109 , 110 ] and balance changes [ 111 , 112 , 113 , 114 , 115 ] in their samples, composed of children using cochlear implants. Despite these findings, after cochlear implant surgery, the children have demonstrated satisfactory results in relation to speech and hearing [ 116 , 117 , 118 , 119 , 120 , 121 ], and as balance is a motor skill capable of being improved through rehabilitation exercises, children can benefit from vestibular rehabilitation and balance programs specific to the population, if referred in a timely manner.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to the data referring to children with SNHL, this study also analyzed five children using cochlear implants, and all of them presented dysfunctions in the vestibular system and postural instabilities in the stabilometric evaluation. These findings corroborate those of other studies, which found vestibular dysfunctions [ 105 , 106 , 107 , 108 , 109 , 110 ] and balance changes [ 111 , 112 , 113 , 114 , 115 ] in their samples, composed of children using cochlear implants. Despite these findings, after cochlear implant surgery, the children have demonstrated satisfactory results in relation to speech and hearing [ 116 , 117 , 118 , 119 , 120 , 121 ], and as balance is a motor skill capable of being improved through rehabilitation exercises, children can benefit from vestibular rehabilitation and balance programs specific to the population, if referred in a timely manner.…”
Section: Discussionsupporting
confidence: 92%